Efficacy and safety of intradialytic exercise in haemodialysis patients: a systematic review and meta-analysis. Issue 1 (21st January 2019) - Pu, Jiang; Jiang, Zheng; Wu, Weihua; Li, Li; Zhang, Liling; Li, Ying; Liu, Qi; Ou, Santao
Abstract : Objective: To assess the efficacy and safety of intradialytic exercise for haemodialysis patients. Design: Systematic review and meta-analysis. Data sources: Databases, including PubMed, Embase, the Cochrane Library, China Biology Medicine and China National Knowledge Infrastructure, were screened from inception to March 2017. Eligibility criteria: Randomised controlled trials (RCTs) aimed at comparing the efficacy and safety of intradialytic exercise versus no exercise in adult patients on haemodialysis for at least 3 months. A minimum exercise programme period of 8 weeks. Data extraction: Study characteristics and study quality domains were reviewed. Studies were selected, and data extracted by two reviewers. Data analysis: The pooled risk ratios and mean differences (MDs) with 95% CIs for dichotomous data and continuous data were calculated, respectively. Results: A total of 27 RCTs involving 1215 subjects were analysed. Compared with no exercise, intradialytic exercise increased dialysis adequacy (Kt/V) (MD 0.07, 95% CI 0.01 to 0.12, p=0.02) and maximum volume of oxygen that the body can use during physical exertion peak oxygen consumption (MD 4.11, 95% CI 2.94 to 5.27, p<0.0001), alleviated depression standardised mean difference (−1.16, 95% CI −1.86 to –0.45, p=0.001) and improved physical component summary-short form-36 (SF-36) level (MD 7.72, 95% CI 1.93 to 13.51, p=0.009). Also, intradialytic exercise could significantly reduce systolic blood pressure (MD −4.87, 95% CI −9.20 to –0.55, p=0.03) as well as diastolic blood pressure (MD −4.11, 95% CI −6.50 to –1.72, p=0.0007). However, intradialytic exercise could not improve mental component summary-SF-36 level (MD 3.05, 95% CI −1.47 to 7.57, p=0.19). There was no difference in the incidence of adverse events between the intradialytic exercise and control groups. Conclusions: Intradialytic exercise resulted in benefits in terms of improving haemodialysis adequacy, exercise capacity, depression and quality of life for haemodialysis.